Law and practice for architects - Greenstreet, Bob.; Greenstreet, Karen; Schermer, Brian (Oxford ; Boston ; London : Elsevier Architectural Press, 2005)
Provides a frame work for the understanding of the legal, contractual, and procedural implications of architectural practice in North America.
The architect and the law -- The building industry -- The architect in practice -- Law and the design phase -- Contract formation -- The construction phase -- Completion -- Dispute resolution.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Architects -- Legal status, laws, etc. -- United States; Construction contracts -- United States; Architectural practice -- United States; LAW -- Taxation; Architects -- Legal status, laws, etc; Architectural practice; Construction contracts; United States